Chemical and microbial mechanisms underpinning calcium-regulated suppression of cadmium bioavailability in alkaline paddy soil and cadmium accumulation in rice grain - Xiaoyu Feng; Zhihao Pang; Junli Liu; Hongyun Peng; Yongchao Liang; Bin Guo (Ecotoxicology and Environmental Safety)
Lime is an effective amendment for reducing cadmium (Cd) bioavailability in acidic soils. However, the mechanisms underlying calcium (Ca)-Cd interactions during liming remain unclear. Here, the effects of different lime materials (CaO, Ca(OH)2, and CaCO3) at three amendment levels (0.05 %, 0.10 % and 0.25 %) on soil bacterial communities, Cd and Ca uptake, and rice growth and yield were investigated in alkaline paddy soils. The dynamics of pH, Ca and Cd concentrations in soil pore water were also determined. Results indicated that all liming treatments significantly enhanced rice growth and yield by 6.71 %-44.83 %, but reduced Cd uptake and translocation by 29.61 %-60.16 %, compared with the control. The most pronounced effect was observed in the treatment with 0.05 % CaCO3, which decreased grain Cd by 56.82 %. This treatment also maintained the highest soil pore water pH and the lowest Cd concentration throughout the experimental period. In addition, CaCO3 application significantly decreased the richness and diversity of soil bacterial communities. Specifically, Desulfobacterota, Gemmatimonadota, and Bacteroidota nearly disappeared, while the relative abundance of WPS-2 and Chloroflexi increased. Overall, CaCO3 is more effective than CaO and Ca(OH)2 in controlling Cd bioavailability in alkaline soils, and an application rate of 0.05 % is sufficient. The associated mechanisms are due to the antagonism of Ca with Cd in the soil-rice system, and the sufficient supply of Ca or carbon (C) resources provided by CaCO3 for Cd resistant bacteria, thus decreasing the biological effectiveness of Cd in soils.